Method for manufacturing a photocurable silicone composition and a release liner
Patent Information
- Application Number
- KR1020227032001
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-19
- Filing Date
- 2021-02-18
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2041-02-18
Abstract
Description
Technology Field
[0001] Cross-reference regarding related applications
[0002] This application was filed on February 19, 2020, the entire contents of which are incorporated herein by reference, and claims priority to U.S. Provisional Application 62 / 978,488 for “Photocurable silicone composition and method for manufacturing release liner”.
[0003] The present invention relates to a curable silicone composition, an article comprising a cured coating formed from the composition, and a method for manufacturing such a coating and an article. In particular, the present invention relates to a photocurable silicone composition, a method for forming a coating from the composition, and an article comprising such a coating. The composition and method are particularly useful for forming a release liner comprising a silicone coating. Background Technology
[0004] Silicone release coatings made by including, in addition to vinyl-silicon and hydride-silicon polymers, silicon-compatible platinum(II) complexes such as the Karstedt hydrosilylation catalyst disclosed in U.S. Patent No. 3,715,334 and platinum inhibitors such as the maleate ester disclosed by Eckberg in U.S. Patent No. 4,256,870, are known and have been used for a considerable period. These coatings can be applied to paper or film substrates without the use of solvents and cured by applying heat to evaporate the inhibitor. To cure at high speed, exposure to temperatures above 150°C for a few seconds is typically required, which is a duration of exposure to temperatures above 150°C that can degrade paper and thermally sensitive films such as polyethylene or polyester. A large amount of energy is consumed by the heat-curing oven, which is too large to enable rapid processing of release liners.
[0005] Silicone polymers having reactive functional groups, including cycloaliphatic epoxy and acrylate groups, are commercially available materials that crosslink when exposed to focused UV light in the presence of iodine and free radical photocatalysts. These products are used in the manufacture of release liners (see, for example, U.S. Patents No. 4,279,717 and 6,548,568). However, these polymers require multiple processing steps involving the input of various organic molecules and are significantly more expensive than vinyl- and hydride-functional silicone polymers curable by platinum-catalyzed hydrosilylation. Furthermore, the useful curing rate of acrylate-functional silicone coatings requires an inert atmosphere with less than 50 ppm of oxygen present in the UV curing chamber. The reactive polar functional groups required to enable the rapid photocrosslinking of these silicones hinder the release of aggressive adhesives, such as conventional emulsion acrylic types.
[0006] Photo-activated platinum(IV) trialkyl cyclopentadiene compounds are described in particular in the literature [Robinson and Shaw, J. Chem Soc 1965, 1529, and by Fritz and Shwarzhaus, J. Organometallic Chem 5, 181 (1966)]. U.S. Patent No. 4,600,484 describes the use of various cyclopentadienyl (Cp) trialkyl Pt(IV) [abbreviation; CpPtR3] compounds for photo-activated hydrosilylation reactions, including the addition reaction of olefins to SiH-functional silane and siloxane monomers, along with converting the liquid mixture into a solid adhesive coating useful for release of pressure-sensitive adhesives by means of a crosslinking reaction between vinyl-functional polydimethylsiloxane and SiH-functional polysiloxane. However, these compositions require a relatively high concentration of photoactive platinum catalyst (200 ppm Pt or more) to achieve rapid curing of a silicon coating > 2 micron thick when applied to a polyethylene-coated kraft paper sheet and then exposed to UV radiation from a 200 watt / in mercury vapor UV lamp.
[0007] U.S. Patent No. 4,916,169 describes the addition of various visible light-absorbing polycyclic aromatic hydrocarbon sensitizers, such as anthracene, thioxanthone, and anthraquinone, to enable visible light curing of thick-section silicone elastomer compositions, such as CpPtR3-photocatalytic silicone coatings and dental molds. Boardman describes the lengthy light absorption (irradiation for several minutes) of viscous vinyl and SiH-functional polydimethylsiloxane compositions containing high catalyst concentrations (> 300 ppm Pt) to produce thick rubbery products. It should be noted that some of the polycyclic photosensitizers described in the above '169 patent are insoluble in a dimethyl silicone matrix.
[0008] U.S. Patent No. 6,451,869 relates to the use of a self-sensitized dicyclopentadienyl trimethyl Pt(IV) photo-active hydrosilylation catalyst for the rapid crosslinking of vinyl silicon and hydride-silicon blends upon exposure to UV light. These catalysts utilize the substitution of aromatic UV absorbing groups, such as naphthyl and phenanthrile, on the Cp ring prior to the synthesis of [Ar-Cp]PtMe3 catalysts. However, Butts reports that the yield of the final self-sensitized photocatalyst is less than 50%, making these compounds expensive and difficult to manufacture for commercial purposes.
[0009] U.S. Patent No. 8,088,878 describes the modification of a CpPtR3 photoactivated hydrosilylation catalyst by substituting a hydrolytic siloxy substituent, such as -Si(OMe)3, on its cyclopentadiene ring so that the catalyst is made nonvolatile and can be cured into a silicone elastomeric article produced by UV irradiation of a viscous mixture of silanol-stopped polydimethylsiloxane, vinylsilicon polymer, SiH-functional siloxane, and a condensation co-catalyst such as Zn(acac)2. A long post-cure of up to 2 hours to complete crosslinking and subsequent condensation of the platinum catalyst compound has been reported after irradiation for 10 seconds. Such treatment is not suitable for the commercial production of silicone release liners. The problem to be solved
[0010] The following is a summary of the invention to provide a basic understanding of some aspects. This summary is not intended to identify principal or major elements, or to define any limitations of the embodiments or claims. Additionally, this summary may provide a simplified overview of some aspects that may be described in more detail in other parts of this specification.
[0011] The present invention generally relates to novel addition-curable silicone formulations, which may be processed for the manufacture of release liners by applying a thin coating of such formulation onto paper and film substrates and subsequently exposing to an ambient atmosphere and ambient temperature or slightly elevated temperature of actinic radiation. The formulation comprises a vinyl- and hydride-functional polysiloxane polymer (e.g., vinyl- and hydride-functional polydimethylsiloxane polymer), an acid-anhydride-functional polysiloxane additive, and a photo-active platinum(IV) cyclopentadienyl catalyst capable of initiating a crosslinking hydrosilylation reaction upon absorption of ultraviolet light. Selection of a specific UV lamp and a reflector ) It has been found that selecting a combination of filters significantly improves the photocuring performance of such systems. In addition, exposing the curable composition to a low level of heat before exposure to UV light can provide improved curing of the composition.
[0012] Accordingly, the object of the present invention is to provide a commercially viable means for treating an addition-curable silicone release coating by UV irradiation of an addition-curable silicone formulation. The composition, method, and process of the present invention provide a photocurable silicone release coating that does not suffer from the disadvantages of the conventional methods and systems as described above. means of solving the problem
[0013] These and other objectives are achieved by formulating a silicone coating composition comprising a vinyl-functional polysiloxane, a hydride-functional polysiloxane crosslinkable polymer, a catalytic quantity of a cyclopentadienyl trialkyl platinum (IV) photo-hydrosilylation catalyst, and a low amount of an acid-anhydride functional polydimethyl-methylhydride siloxane anchorage and curing additive.
[0014] In one aspect, a cyclopentadienyl trialkyl platinum (IV) catalyst is used in combination with vinyl-functional and hydride-functional polysiloxanes (e.g., polydimethylsiloxane) and any other polysiloxane having an alkyl-acid-anhydride functional group, and when applied as a 1-2 micron coating and treated with a focused iron-doped mercury vapor UV curing lamp or (preferably) a combination of mild pre-heating and subsequent UV exposure, it can provide a release coating composition capable of high-speed curing for ordinary supercalendared kraft paper and poly-coated kraft paper.
[0015] In one aspect, a photocurable silicon composition is provided comprising (i) vinyl functional polysiloxane; (ii) hydride functional siloxane; (iii) photoactive catalyst; and (iv) acid anhydride functional polysiloxane.
[0016] In one embodiment, the vinyl functional polysiloxane has the following formula (I):
[0017] M 1Vi a M 2 b D 1Vi c D 2 d T 1Vi e T 2 f Q 1 g (I)
[0018] (Here,
[0019] M 1Vi = (R 1 )(R 2 )(CH2=CH)SiO 1 / 2
[0020] M 2 = (R 3 )(R 4 )(R 5 SiO 1 / 2
[0021] D 1Vi = (R 6 )(CH2=CH)SiO 2 / 2
[0022] D 2 = (R 7 )(R 8 )SiO 2 / 2
[0023] T 1Vi = (CH2=CH)SiO 3 / 2
[0024] T 2 = (R 9 )SiO 3 / 2
[0025] Q 1 = SiO 4 / 2 And,
[0026] Here, R 1, R 2, R 3, R 4, R 5, R 6, R 7, R 8, and R 9 Each is independently a C1-C10 saturated hydrocarbon radical; 50 < a + b + c + d + e + f + g < 10,000, and a + c + e is greater than 0.
[0027] In one embodiment, the vinyl functional polysiloxane has the following formula (Ia);
[0028] M 1vi D 1vi CD 2 dM 1vi(Ia)
[0029] Here, M 1vi is (R 1 )(R 2 )(CH2=CH)SiO 1 / 2 Igo; D 1vi is (R 6 )(CH2=CH))SiO 2 / 2 is; D 2 is (R 7 )(R 8 )SiO 2 / 2 and; R 1 , , R 2 , R 3 , R 5 , R 6 , R 7, and R 8 Each is independently a C1-C10 saturated hydrocarbon radical; c is 0-10; and d is 50-250.
[0030] In one embodiment of the composition of any of the preceding embodiments, the hydride functional siloxane has the following formula (II);
[0031] M 3H h M 4 i D 3H j D 4 k T 3H l T 4 m Q 2 n (II)
[0032] Here,
[0033] M 3H = (R 10 )(R 11 )(H)SiO 1 / 2
[0034] M 4 = (R 12 )(R 13 )(R 14 )SiO 1 / 2
[0035] D 3H = (R15 )(H)SiO 2 / 2
[0036] D 4 = (R 16 )(R 17 )SiO 2 / 2
[0037] T 3H = (H)SiO 3 / 2
[0038] T 2 = (R 18 )SiO 3 / 2
[0039] Q 2 = SiO 4 / 2 And,
[0040] Here, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , and R 18 Each is independently a C1-C10 saturated hydrocarbon radical; the subscripts h, i, j, k, l, m and n are 0 or positive numbers, where 2 ≤ h + i + j + k + l + m + n < 1,000 and h + j + l is greater than 0.
[0041] In one embodiment, the hydride functional siloxane has the following formula (IIb);
[0042] M 4 D 3H j M 4 (IIb)
[0043] Here, M 4 D 3H, and , M 4, is as defined above, and j is 10-40.
[0044] In one embodiment, the hydride functional siloxane is a copolymer of the following formula (IIa):
[0045] M 4 D3H j D 4 k M 4 Q 2 (IIa)
[0046] Here, M 4 D 3H , D 4 , M 4 , and Q 2 is as defined above, and j + k is 10-40.
[0047] In one embodiment of a photocurable composition of any one of the above embodiments, the photoactive catalyst is, Formula (i): R 19 CpPtR 20 3(here R 19 and R 20 Each is independently selected from C1-C10 alkyl groups, Cp is a cyclopentadiene group, and the bond between Cp and Pt is eta It is a combination); Equation (ii): [(R 29 ) a (R 30 ) b Cp]Pt(R 31 ) 3 (Here, R 29 is a C7-20 aromatic organic radical, and R 30 and R 31 are each independently C1-22 aliphatic organic radicals, Cp is a cyclopentadienyl radical, "a" is an integer from 1 to 3, "b" is an integer from 0 to 3, and the sum of a + b is 1 to 4); and / or formula (iii): [(R 32 ) c (R 33 ) d Cp]PtR 34 R 35 Q (here, R 32 is a C6-20 aromatic radical, and R 33 , R 34 , and R 35It is selected from one or more platinum-cyclopentadiene complexes in which each is independently a C1-22 aliphatic organic radical, Cp is a cyclopentadienyl radical, Q is a silicon-containing organic sensitizing group, "c" and "d" are each independently integers from 0 to 5, and the sum of "c + d" is 0 to 5.
[0048] In one embodiment, the photoactive catalyst is a Pt(IV) compound, methylcyclopentadienyltrimethyl platinum.
[0049] In one embodiment of a photocurable composition of any one of the above embodiments, the acid-anhydride functional silicone is a compound of the following formula:
[0050] M 5A D 5 o D 6A p D 7H q M 5A
[0051] Here, M 5A (R 21 )(R 22 ) (R 23 )SiO 1 / 2 and, D 5 (R 24 )(R 25 )SiO 2 / 2, and, D 6A (R 26 )(R 27 )SiO 2 / 2 and, D 7H = (R 28 )(H)SiO 2 / 2 and, here, R 21 , R 22 , R 24 , R 25 , R 26 , and R 28are each independently C1-C10 saturated hydrocarbon radicals; R 23 and R 27 Each represents an acid-anhydride functional group that can be derived independently from the reaction with the Si(H) functional group of allyl succinic acid-anhydride; o + q is 10-40 and p is 1-20.
[0052] In one embodiment of the photocurable composition of any of the above embodiments, the composition is further composed of a siloxanol resin.
[0053] In one embodiment of the photocurable composition of any one of the above embodiments, the ratio of hydride groups to vinyl groups is about 0.5:1 to about 10:1.
[0054] In one embodiment of the photocurable composition of any of the above embodiments, the ratio of hydride groups to vinyl groups is about 1.5:1 to about 3:1.
[0055] In one embodiment of the photocurable composition of any of the above embodiments, the ratio of hydride groups to vinyl groups is about 2:1 to about 2.5:1.
[0056] In one embodiment of the photocurable composition of the present invention, vinyl functional polysiloxane (i) is present in an amount of about 80 to about 99 parts by weight; hydride functional polysiloxane (ii) is present in an amount of about 1 to about 20 parts by weight; acid-anhydride functional polysiloxane (iv) is present in an amount of about 0.1 to 10 parts by weight; and photoactive catalyst (iii) is present in an amount sufficient to provide an amount of platinum of about 50 to about 150 ppm, each part by weight is based on the total weight of the composition.
[0057] In another aspect, a method for forming a silicon film on a substrate is provided, comprising the steps of: (a) applying a photocurable silicon composition of any one of the preceding embodiments onto the surface of a substrate; and (b) exposing the photocurable silicon composition to a UV light source having a wavelength of about 25 nm to about 500 nm.
[0058] In one embodiment, the UV light source is H + Mercury vapor type UV lamp ) am.
[0059] In one embodiment, the UV light source is a D-type iron-doped mercury vapor UV lamp.
[0060] In one embodiment of the method of any of the preceding embodiments, the substrate carrying the silicon composition is transported at a speed of about 20 feet / min to about 1,000 feet / min.
[0061] In one embodiment of any one of the above embodiments, the method further comprises the step of concentrating light from a UV light source onto a composition using one or more reflectors.
[0062] In one embodiment of any one of the above embodiments, the method further comprises the step of exposing a silicon composition and a substrate coated with the composition to a heat source before exposing the composition to a UV light source.
[0063] In one embodiment, the heat source is selected from an oven, an infrared lamp, an LED light source, or a combination thereof.
[0064] In one embodiment, the composition and the substrate to which the composition is applied are heated to a temperature of about 25°C to about 120°C.
[0065] In one embodiment of any one of the above embodiments of the method, the substrate is selected from one or more of glassine paper, supercalendered kraft (SCK) paper, clay-coated kraft (CCK) paper, polyethylene, polypropylene, polyester, polyethylene-kraft paper (PK), or polypropylene-kraft paper (PPK).
[0066] In another aspect, an article is provided comprising a coating formed from a photocurable composition of any one of the preceding embodiments disposed on the surface of a substrate.
[0067] In one embodiment, the article is a release liner, and the substrate is selected from one or more of glassine paper, supercalendered kraft (SCK) paper, clay-coated kraft (CCK) paper, polyethylene, polypropylene, polyester, polyethylene-kraft paper (PK), or polypropylene-kraft paper (PPK).
[0068] In another aspect, an adhesive article is provided comprising an adhesive-backed substrate that is in releaseable contact with a release layer, wherein the release layer comprises a coating formed from a photocurable composition of any one of the preceding embodiments.
[0069] In another aspect, an article formed from the method of any preceding embodiment is provided.
[0070] The detailed description below discloses various exemplary suns. Some improvements and novel suns may be obvious, but others may become apparent from the detailed description below. Specific details for implementing the invention
[0071] Hereinafter, embodiments of the present invention are described with reference to preferred exemplary embodiments. It should be understood that other embodiments may be used and structural and functional changes may be made. Furthermore, features of various embodiments may be combined or modified. As such, the following detailed description is presented merely by example and should not limit in any way the various alternatives and modifications that may be made to the exemplified embodiments. In this specification, many specific details provide a complete understanding of the present invention. It should be understood that aspects of the present invention may be practiced with other embodiments that do not necessarily include all aspects described in this specification.
[0072] As used herein, the words “example” or “exemplary” mean an instance or illustration. The words “example” or “exemplary” do not indicate a primary or preferred aspect or embodiment. Unless otherwise indicated by the context, the word “or” is intended to be inclusive rather than exclusive. For example, the phrase “A uses B or C,” includes any inclusive permutation (e.g., A uses B; A uses C; or A uses both B and C). As another matter, the article “one (a)” is generally intended to mean one or more, unless otherwise indicated by the context.
[0073] As used in this application, the term “alkyl” includes straight-chain, branched-chain, and cyclic alkyl groups. Specific and non-limiting examples of alkyl include, but are not limited to, methyl, ethyl, propyl, hexyl, octyl, and isobutyl. In embodiments, the alkyl group is selected from C1-C30 alkyl, C1-C18 alkyl, C2-C10 alkyl, and even C4-C6 alkyl. In embodiments, the alkyl is selected from C1-C6 alkyl.
[0074] As used herein, the term “aryl” refers to a non-limiting group of any aromatic hydrocarbon from which one hydrogen atom has been removed. An aryl may have one or more aromatic rings that can be fused or connected by a single bond or other groups. Specific and non-limiting examples of aryls include, but are not limited to, tolyl, xylyl, phenyl, and naphthalenyl. In an embodiment, the aryl group may be selected from C6-C30 aryls, C6-C20 aryls, and even C6-C10 aryls.
[0075] Viscosity can be measured in any suitable manner. In one embodiment, viscosity can be measured using an Ostwald viscometer. Ostwald viscosity is defined by multiplying the time required for a viscous fluid to flow through a specified distance of a calibrated tube at 25°C by a tube constant determined for a liquid of known viscosity selected by the user. In one embodiment, the reference liquid is deionized water. Alternatively, the constant for the apparatus may be determined and provided by the apparatus manufacturer.
[0076] A photocurable silicone composition, a method or process for treating such composition to form a cured coating, and an article comprising such coating are provided.
[0077] Photocurable silicone composition
[0078] The photocurable silicone composition of the present invention comprises (i) vinyl functional polysiloxane; (ii) hydride functional polysiloxane; (iii) photoactive catalyst; and (iv) acid-anhydride functional polysiloxane. The composition may optionally comprise, but is not limited to, other additives and materials comprising (v) an additional crosslinking agent and (vi) a silanol stopped fluid. The photocurable silicone composition can be cured by exposure to UV radiation to form a coating on the surface of a substrate.
[0079] The silicone composition is generally provided to have a flowable consistency so that it can be applied to a substrate as a coating, for example, by roll-coating, spraying, etc. For example, the silicone composition may be an uncured or partially cured liquid having a sufficiently low viscosity so that it can be easily applied as a coating on a substrate.
[0080] Vinyl functional polysiloxanes may be selected as desirable for a specific purpose or intended use to provide a composition suitable for forming a desired coating or film. Vinyl functional siloxanes are composed of vinyl radicals attached to silicon via carbon-silicon bonds. The vinyl radicals may be at terminal (i.e., vinyl chain-stop) positions, pendantd to silicon atoms within the backbone of the siloxane polymer, or a combination thereof. Typically, vinyl functional polysiloxanes have a viscosity in the range of about 50 to about 100,000 centipoises (cPs) at 25 °C, where 1 centipoise (cPs) = 1 millipascal-second (mPa·s). In an embodiment, the viscosity is about 100 to about 50,000 cPs at 25 °C; about 500 to about 25,000 cPs at 25 °C; It may be in the range of about 1,000 to about 10,000 cPs at 25°C; or about 2,500 to about 5,000 cPs. In one embodiment, the vinyl functional polysiloxane has a viscosity of about 200 to about 600 cPs at 25°C.
[0081] Herein and elsewhere in this specification and claims, numerical values may be combined to form new ranges and non-specified ranges.
[0082] In one embodiment, the vinyl functional polysiloxane has the following formula (I):
[0083] M 1Vi a M 2 b D 1Vi c D 2 d T 1Vi e T 2 f Q 1 g (I)
[0084] Here,
[0085] M 1Vi = (R1 )(R 2 )(CH2=CH)SiO 1 / 2
[0086] M 2 = (R 3 )(R 4 )(R 5 SiO 1 / 2
[0087] D 1Vi = (R 6 )(CH2=CH)SiO 2 / 2
[0088] D 2 = (R 7 )(R 8 )SiO 2 / 2
[0089] T 1Vi = (CH2=CH)SiO 3 / 2
[0090] T 2 = (R 9 )SiO 3 / 2
[0091] Q 1 = SiO 4 / 2 And,
[0092] R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , , and R 9 are each independently C1-C10 saturated hydrocarbon radicals; 50 < a + b + c + d + e + f + g < 10,000, and a + c + e is greater than 1. R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , , and R 9is a C1-C10 alkyl, C2-C8 alkyl, or C4-C6 alkyl. In one embodiment, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , and R 9 Each is methyl. In one embodiment, 100 < a + b + c + d + e + f + g < 7,500; 250 < a + b + c + d + e + f + g < 5,000; or 500 < a + b + c + d + e + f + g < 2,500.
[0093] In one embodiment, the vinyl functional polysiloxane has the following formula (Ia):
[0094] M 1vi D 1vi CD 2 dM 1vi (Ia)
[0095] Here, M 1vi is (R 1 )(R 2 )(CH2=CH)SiO 1 / 2 Igo; D 1vi is (R 6 )(CH2=CH))SiO 2 / 2 is; D 2 is (R 7 )(R 8 )SiO 2 / 2 and; R 1 , R 2 , R 3 , R 5 , R 6 , R 7 , and R 8 Each is independently a C1-C10 saturated hydrocarbon radical; c is 0-10; and d is 50-250. In an embodiment, R 1 , R 2 , R 3 , R 5 , R6 , R 7 , and R 8 is a C1-C10 alkyl, C2-C8 alkyl, or C4-C6 alkyl. In one embodiment, R 1 , R 2 , R 3 , R 5 , R 6 , R 7 , and R 8 Each is methyl. In one embodiment, c is 1-10, 2-8, or 4-6.
[0096] Vinyl functional siloxane is present in the composition in an amount of about 80 to about 99 parts, about 85 to about 95 parts, or about 89 to about 92 parts based on the total weight of the composition.
[0097] Hydride-functional polysiloxane is a siloxane polymer composed of Si-H groups at terminal positions, in the polymer backbone, or a combination thereof. Hydride-functional siloxane polymers may be linear molecules or branched. Typically, hydride-functional polysiloxane has a viscosity of less than about 1,500 centipoises (cPs) at 25°C, more typically about 20 to about 1,000 cPs at 25°C, and much more typically about 30 to about 500 cPs at 25°C. Herein and elsewhere in this specification and claims, numerical values may be combined to form new ranges and unspecified ranges.
[0098] In one embodiment, the hydride functional siloxane has the following formula (II):
[0099] M 3H h M 4 i D 3H j D 4 k T 3H l T4 m Q 2 n (II)
[0100] Here,
[0101] M 3H = (R 10 )(R 11 )(H)SiO 1 / 2
[0102] M 4 = (R 12 )(R 13 )(R 14 )SiO 1 / 2
[0103] D 3H = (R 15 )(H)SiO 2 / 2
[0104] D 4 = (R 16 )(R 17 )SiO 2 / 2
[0105] T 3H = (H)SiO 3 / 2
[0106] T 2 = (R 18 )SiO 3 / 2
[0107] Q 2 = SiO 4 / 2 And,
[0108] R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , and R 18 Each is independently a C1-C10 saturated hydrocarbon radical; the subscripts h, i, j, k, l, m, and n are 0 or positive numbers, wherein 2 ≤ h + i + j + k + l + m + n < 1,000, and h + j + l is greater than 0. In an embodiment, R 10 , R 11, R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , and R 18 is a C1-C10 alkyl, C2-C8 alkyl, or C4-C6 alkyl. In one embodiment, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , and R 18 are methyl respectively.
[0109] In one embodiment, the hydride functional polysiloxane is a copolymer of the following formula (IIa):
[0110] M 4 D 3H j D 4 k M 4 (IIa
[0111] Here, j + k is 10-40.
[0112] In another embodiment, the hydride functional polysiloxane is a polymer of formula (IIb) below:
[0113] M 4 D 3H j M 4 (IIb)
[0114] Here, j is 10⁻⁴⁰.
[0115] In another embodiment, the hydride functional polysiloxane has the following formula (IIc):
[0116] M 3H h Q 2 (IIc)
[0117] Here, h is 1-4.
[0118] Hydride functional polysiloxane is present in an amount of about 1 to about 20 parts, about 2 to about 15 parts, or about 5 to about 10 parts based on the total weight of the composition.
[0119] It will be understood that hydride-functional polysiloxanes may be provided as a mixture of hybrid functional silicones of different formulas. Different hydride-functional polysiloxanes may have similar structures but may have different molecular weights (weight average molecular weight), or they may have different structures. In one embodiment, the hydride-functional polysiloxane is provided as a mixture of a hydride-functional polysiloxane of formula (IIa) and a hydride-functional polysiloxane of formula (IIb).
[0120] The ratio of hydride to vinyl groups can be selected as needed. In one embodiment, the ratio of hydride to vinyl groups is about 0.5:1 to about 10:1, about 1:1 to about 7.5:2, or about 2.5:1 to about 5:1. In an embodiment, the ratio of hydride to vinyl groups is about 1.5:1 to about 3:1. In another embodiment, the ratio of hydride to vinyl groups is about 2:1 to about 2.5:1. In one embodiment, the ratio of hydride to vinyl groups may be 1:1, 1.2:1, 1.5:1, 1.75:1, 2:1, 2.25:1, 2.5:1, or 3:1. Accordingly, the variables a, c, e, h, j, and l in equations (I) and (II) can be selected to provide a desirable ratio of hydride to vinyl group.
[0121] The composition of the present invention comprises a photo-activated platinum catalyst suitable for catalyzing the reaction between vinyl-functional siloxanes and hydride-functional siloxanes upon exposure to light of a sufficient wavelength. Particularly suitable is a UV-activable Pt catalyst that is inactive in the absence of light and can be converted into a Pt catalyst that is active at room temperature after irradiation with light having a wavelength of 250 to 500 nm. Examples of suitable UV-activated Pt catalysts include, for example, (alkyl-cyclopentadienyl)trialiphatic Pt compounds or derivatives thereof as disclosed in EP 0146307, but are not limited thereto. Particularly suitable are cyclopentadienyltrimethylplatinum, methylcyclopentadienyltrimethylplatinum, and derivatives thereof, which comprise a substituted cyclopentadienyl moiety and may optionally be attached to the polymer directly or through an additional moiety. Other suitable photoactive hydrosilylation catalysts include, for example, bis(acetylacetonato)platinum compounds and corresponding derivatives thereof. Individual catalysts or a mixture of at least two catalysts may be used.
[0122] In one embodiment, the photoactive catalyst is given by formula R 19 CpPtR 20 It is a platinum-cyclopentadiene complex of 3, where R 19 and R 20 Each is independently selected from C1-C10 alkyl groups, Cp is a cyclopentadiene group, and the bond between Cp and Pt is eta It is a combination. In one embodiment, R 19 and R 20 Each is independently selected from C1-C6 alkyl or C2-C4 alkyl. In one embodiment, R 19 and R 20 Each is methyl.
[0123] Additional catalysts suitable for catalyzing the hydrosilylation reaction are described in U.S. Patent No. 6,127,446 and European Patent No. 1050538, each incorporated herein by reference. In one embodiment, the photoactive catalyst is of the formula [(R 29 ) a (R 30 ) b Cp]Pt(R 31 ) 3 It is a compound of, where R 29 is a C7-20 aromatic organic radical, and R 30 and R 31 Each is independently a C1-22 aliphatic organic radical, Cp is a cyclopentadienyl radical, "a" is an integer from 1 to 3, "b" is an integer from 0 to 3, and the sum of a + b is 1 to 4. In one embodiment, the photoactive catalyst is of the formula [(R 32 ) c (R 33 ) d Cp]PtR 34 R 35 It is a compound of Q, where R 32 is a C6-20 aromatic radical, and R 33 , R 34 , and R 35 Each is independently a C1-22 aliphatic organic radical, Cp is a cyclopentadienyl radical, Q is a silicon-containing organic sensitizing group, "c" and "d" are each independently integers from 0 to 5, and the sum of "c + d" is from 0 to 5.
[0124] Some examples of such catalysts include, but are not limited to, aryl(methylcyclopentadienyl)trimethyl platinum and aryl(methylcyclopentadienyl)dimethyl(trimethylsilylmethyl)platinum (wherein the aryl functional group may be, for example, naphtha, phenanthrile, etc.). Some specific examples include [(1'-naphthyl)-cyclopentadienyl]trimethyl platinum; [(2'-naphthyl)-cyclopentadienyl]trimethyl platinum; [1-methyl-3-(1'-naphthyl)-cyclopentadienyl]trimethyl platinum; [1-methyl-3-(2'-naphthyl)-cyclopentadienyl]trimethyl platinum; [(4'-biphenyl)-cyclopentadienyl]trimethyl platinum; [1-(4'-biphenyl)-3-methyl-cyclopentadienyl]trimethyl platinum; [(9'-phenanthryl)-cyclopentadienyl]-trimethyl platinum; [1-methyl-3-(9'-phenanthryl)-cyclopentadienyl]-trimethyl platinum; [1-(2'-anthracenyl)-3-methyl-cyclopentadienyl]-trimethyl platinum; [(2'-anthracenyl)-cyclopentadienyl]trimethyl platinum; [(1--pyrenyl)-cyclopentadienyl]trimethyl platinum; [1-methyl-3-(1'-pyrenyl)-cyclopentadienyl]trimethyl platinum; (cyclopentadienyl)dimethyltrimethylsilylmethyl platinum; (cyclopentadienyl)diethyltrimethylsilylmethyl platinum; (cyclopentadienyl)dipropyltrimethylsilylmethyl platinum; (cyclopentadienyl)diisopropyltrimethylsilylmethyl platinum; (Cyclopentadienyl)diallyltrimethylsilylmethyl platinum; (Cyclopentadienyl)dibenzyltrimethylsilylmethyl platinum; (Cyclopentadienyl)dimethyltriethylsilylmethyl platinum; (Cyclopentadienyl)dimethyltripropylsilanylmethyl platinum; (Cyclopentadienyl)dimethyltriisopropylsilylmethyl platinum; (Cyclopentadienyl)dimethyltriphenylsilylmethyl platinum; (Cyclopentadienyl)dimethyldimethylphenylsilanylmethyl platinum; (Cyclopentadienyl)dimethylmethylphenylsilylmethyl platinum; (Cyclopentadienyl)dimethyldimethyl(trimethylsiloxy)silylmethyl platinum; (Cyclopentadienyl)dimethyldimethyl(trimethylsiloxy)silylmethyl platinum; (Cyclopentadienyl)dimethyldimethyl(dimethylvinylsiloxy)silylmethyl platinum; [(1'-Naphthyl)cyclopentadienyl]trimethylsilylmethyl platinum;
[0125] [(2'-Naphthyl)Cyclopentadienyl]Trimethylsilylmethylplatinum; [1-Methyl-3-(1'-Naphthyl)Cyclopentadienyl]Trimethylsilylmethylplatinum; [1-Methyl-3-(2'-Naphthyl)Cyclopentadienyl]Trimethylsilylmethylplatinum; [(4'-Biphenyl)Cyclopentadienyl]Trimethylsilylmethylplatinum; [1(4'-Biphenyl)-3-Methylcyclopentadienyl]Trimethylsilylmethylplatinum; [(9'-Phenanthryl)Cyclopentadienyl]Trimethylsilylmethylplatinum; [1-Methyl-3-(9'-Phenanthryl)Cyclopentadienyl]Trimethylsilylmethylplatinum; [1-(2'-Anthracenyl)-3-Methylcyclopentadienyl]Trimethylsilylmethylplatinum; [(2'-Anthracenyl)Cyclopentadienyl]Trimethylsilylmethylplatinum; [(1'-Pyrenyl)Cyclopentadienyl]Trimethylsilylmethylplatinum; [1-Methyl-3-(1'-Pyrenyl)Cyclopentadienyl]Trimethylsilylmethylplatinum, etc., but not limited thereto.
[0126] The catalyst may be provided in any amount sufficient to convert the composition into a tack-free state. In an embodiment, the catalyst is provided in an amount sufficient to provide platinum in an amount of about 50 to about 150 ppm, about 60 to about 120 ppm, about 75 to about 100 ppm, or about 80 to about 90 ppm.
[0127] The acid-anhydride functionalized polysiloxane is selected from the acid-anhydride functionalized polysiloxanes described in International Patent Application PCT / EP2019 / 074418, the entirety of which is incorporated herein by reference, in one embodiment. In one embodiment, the acid-anhydride functionalized polysiloxane polymer may be selected from compounds represented by the following formula (III);
[0128] M 5A D 5 o D 6A p D 7H q M 5A (III)
[0129] Here, M 5A is (R 21 )(R 22 ) (R 23 )SiO 1 / 2 and, D 5 is (R 24 )(R 25 )SiO 2 / 2, is, D 6A is (R 26 )(R 27 )SiO 2 / 2 and, D 7H is (R 28 )(H)SiO 2 / 2 and, here, R 21 , R 22 , R 24 , R 25 , R 26 , , and R 28 are each independently C1-C10 saturated hydrocarbon radicals; R 23 and R 27 Each represents an acid-anhydride functional group that can be independently derived from the reaction of an allyl succinic acid-anhydride and a Si(H) functional group; o + q is 10-40 and p is 1-20.
[0130] In the implementation example, R 21 , R 22 , R 24 , R 25 , R 26 and R 28 is a C1-C10 alkyl, C2-C8 alkyl, or C4-C6 alkyl. In one embodiment, R 21 , R 22 , R 24 , R 25 , R 26, and R 28 Each is methyl. Acid-anhydride functional polysiloxane may be referred to as polymer AA in this specification.
[0131] Acid-anhydride functional siloxanes are present in an amount of about 0.1 to about 10 parts, about 0.5 to about 7.5 parts, or about 1 to about 5 parts based on the weight of the composition.
[0132] The coating composition may optionally include one or more other additives that are desirable for a specific purpose or intended use. Examples of suitable additives include, but are not limited to, inhibitors, stabilizers, inert fillers, resins such as polyorganosiloxanes other than the aforementioned hydride-functional or vinyl-functional polysiloxanes, non-reinforcing fillers, adhesion promoters, fungicides, fragrances, rheological additives, corrosion inhibitors, antioxidants, light stabilizers, flame retardants, agents for influencing the electrical properties, dispersion aids, solvents, pigments, dyes, plasticizers, organic polymers, heat stabilizers, etc.
[0133] In one embodiment, the composition may include a sensitizer as an additive. A sensitizer is a substance that absorbs specific active energy rays and is in an electron excited state. Examples of suitable sensitizers that may be used include, but are not limited to, benzophenone, thioxantone, isopropylthioxantone, anthraquinone, 3-acylcoumarin derivatives, terphenyl, styrylketone, 3-(aroylmethylene)thiazolin, camphoquinone, eosin, rhodamine, and erythrosine.
[0134] Examples of suitable resins, such as polyorganosiloxanes, include hydroxy-functional polysiloxanes having -OH groups attached to silicon atoms, which may be referred to as silanol or silanol resins. The silanol functional group may be at a terminal position within the siloxane chain or attached to a silicon atom. The silanol resin may be of the MDTQ type. In one embodiment, the silanol resin is a silanol chain-stopped polysiloxane having a silanol functional group at a terminal position. In one embodiment, the silanol resin may have a viscosity of about 25 to about 10,000 cPs at 25°C, about 50 to about 7,500 cPs at 25°C, about 100 to about 5,000 cPs at 25°C, about 500 to about 2,500 cPs at 25°C, or about 1,000 to about 2,000 cPs at 25°C.
[0135] Some examples of suitable additives may include activated carbon, finely ground quartz, diatomaceous earth, clay, chalk, lithopones, carbon black, graphite, metal oxides, metal carbonates, metal sulfates, metal salts of carboxylic acids, fibers such as glass fibers and plastic fibers, plastic powders, metal dusts, dyes, pigments, etc.
[0136] Method of forming a coating from a composition
[0137] The coating composition can be used to form a coating on a substrate. The coating is formed by applying the coating composition onto the surface of the substrate and curing the composition by exposing the coating to UV radiation.
[0138] The photocurable composition may be applied to a substrate by a suitable method, for example, by roll-coating, or alternatively by spraying from a suitable applicator (e.g., a nozzle), wherein the applicator may be stationary or moving relative to the substrate. While misting or aerosolizing often occurs primarily due to the movement of the applicator relative to the substrate, misting or aerosolizing may be caused by factors other than the movement of the applicator or the substrate. For example, misting may be caused partially or primarily by the method of application rather than by any movement of the applicator relative to the substrate, for example, during a stationary or low-speed spraying process.
[0139] The photocurable composition may be applied to a substrate in any amount or thickness desirable for a particular purpose or intended use. It will be understood that thicker coatings require longer curing times. In one embodiment, the photocurable composition is applied to a substrate in a coating weight of about 0.5 to about 2 grams per square meter (gsm), about 0.75 to about 2 gsm, or about 1 to about 1.75 gsm.
[0140] UV light sources can provide light with wavelengths ranging from about 200 nm to about 400 nm. UV light sources that can be used for curing the composition include, but are not limited to, electrodeless UV lamps, H-type mercury vapor bulbs, D-type iron-doped mercury vapor bulbs, V-type bulbs, X-type bulbs, etc.
[0141] Additionally, the process and system for implementing the process may utilize one or more reflectors or other suitable devices to concentrate UV light. The type and number of such reflectors may be selected as necessary to concentrate light energy to a selected degree during the coating / curing process. In one embodiment, the reflector may be a dichroic reflector.
[0142] In one embodiment, a method for curing a composition comprises the step of first heating the composition and the substrate to which the composition is applied before being exposed to a UV light source. Heat may be provided by any suitable device or method for applying heat. In one embodiment, heat may be provided by an oven such as a convection oven or a forced air oven. In another embodiment, heat may be provided by an infrared light source, such as an LED light source emitting a wavelength of 800 nm or greater, or by a "black body" type heating lamp. Such an infrared light source may be focused onto a moving coated substrate at a point ahead of where the UV light source is located, so that when UV lamp radiation is focused onto the coating, the substrate is heated to a temperature of about 25°C to about 120°C above ambient temperature. The temperature of the heat source should be relatively mild. In embodiments, the coated substrate is heated to a temperature of about 25°C to about 120°C, about 40°C to about 105°C, or about 50°C to about 90°C.
[0143] A substrate coated with a curable composition is generally moved continuously through a system via a conveyor belt or other suitable device for transporting the coated substrate. The coated substrate may be moved through the system and exposed to curing conditions at any speed suitable for exposing the curable composition to UV light (and / or a heat source) to effectively promote the curing of the composition. In one embodiment, a substrate having a silicone composition is transported through the system at a speed of about 20 feet / min to about 1,000 feet / min, about 50 feet / min to about 750 feet / min, about 100 feet / min to about 500 feet / min, or about 200 to about 400 feet / min.
[0144] article
[0145] An article formed by the above method comprises a substrate having a coating formed from a composition disposed on the surface of the substrate. The substrate may be any substrate requiring a coating of the coating formulation. Some examples of suitable substrates include paper, cardboard, wood products, polymer and plastic products, glass products, and metal products.
[0146] Coatings formed from photocurable compositions may be suitable for use in forming release coatings. The coating exhibits release properties on substrates such as engineering paper, asphalt packaging paper, and different releasing double-surface peeling papers, which require a suitable level of release properties.
[0147] Release liners or release layers, such as those used in adhesive article constructions, e.g., labels, tapes, etc., are often formed from a cellulose-based substrate. Examples of substrates that can be coated with a curable silicone composition include, but are not limited to, cellulose-based substrates such as paper, glyphine paper, supercalendered kraft (SCK) paper and clay-coated kraft (CCK) paper, film substrates including polyethylene and polypropylene, and polyester and hybrid substrates, such as polyethylene-kraft paper (PK) or polypropylene-kraft paper (PPK).
[0148] < Examples >
[0149] To enable a person skilled in the art to better practice the present invention, the following examples are given by way of example and are not limited thereto. All parts are by weight unless otherwise indicated.
[0150] Example 1A
[0151] UV photocurable silicone coating formulation A, M (Vi) D 80 M (Vi) 91.6 parts vinylsilicon of composition, 8.4 parts acid-anhydride functional polymer AA, [M (H)It was prepared to have 7.2 parts of a hydride-functional silicone crosslinker of the ]2Q composition, and a [MeCp]PtMe3 catalyst sufficient to provide about 85 ppm of platinum to the coating bath (which does not contain the crosslinker). This coating mixture was manually applied to a Verso 40 lb / ream base weight SCK sheet using a 0 Meyer rod to achieve a laydown of about 2 to 6 g / m². Subsequently, the coated sheet was placed on a single-focus 13 mm diameter Heraeus mounted on a lab-scale UV processor equipped with a speed-adjustable conveyor belt. TM It was passed under a 300-watt / in H+ lamp (medium-pressure mercury vapor type). Curing was qualitatively determined as a function of conveyor line speed based on smearing, silicone migration onto cellophane test tape, and settling onto the SCK sheet. It was found that excellent curing (no smearing, no silicone migration, no rub-off from the substrate) was achieved at conveyor speeds up to 30 ft / min (fpm). Increasing the conveyor speed to 40 fpm resulted in slight migration, causing the cured coating to age and settle rapidly upon UV exposure. Higher conveyor speeds resulted in incomplete curing, but this was gradually improved by a few minutes of post-exposure. The coating technique of this embodiment provided a cured silicone-coated sample that is thicker than that typically produced in the commercial manufacture of silicone release liners.
[0152] Example 1B
[0153] Silicone formulation A was manually applied to the Verso SCK as described in Example 1, but in this case, a 13 mm 300 watt / in diameter Heraeus D lamp [iron-doped medium-pressure mercury vapor type] was used instead of the H+ lamp. An R500 reflector type that does not attenuate long-wavelength lamp emission was used to concentrate UV light onto the coating surface. The coated sheet was passed under the concentrated D lamp at different conveyor speeds, and the results are as follows:
[0154] Conveyor speed, fpm Qualitative hardening
[0155] 80 Excellent curing; no staining, no migration, good settling
[0156] 120 Good curing; slight staining, no migration, good settling
[0157] 150°C insufficient curing; some migration observed, post-curing
[0158] A dramatic improvement in curing speed (> 3x) was obtained by replacing the H+ lamp with an equivalent D lamp. D lamp radiation is red-shifted to a longer wavelength than H+ radiation, which was shown to improve the photocuring efficiency of MeCpPtMe3.
[0159] Example 1C
[0160] Silicone formulation A was manually applied to a Verso SCK sheet as in the previous example, but in this case, the R500 reflector was replaced with a dichroic + reflector. Compared to a conventional R500 type reflector, the dichroic reflector reduces long-wavelength (visible and IR) radiation focused on the sample and increases the relative amount of shorter-wavelength radiation. Subsequently, the coated sheet was passed under a D lamp focused at different conveyor speeds, and the observation results are as follows:
[0161] Conveyor speed, fpm Qualitative hardening
[0162] 80 Excellent curing; no migration, no staining, good settling
[0163] 120 excellent curing;
[0164] 150 Good curing; weak migration occurred, coating defects, good settling
[0165] 180°C undercured; staining and migration observed, fast post-curing
[0166] Replacing it with a dichroic reflector unexpectedly provided additional improvement to the photocuring reaction of this system.
[0167] Example 1D
[0168] Silicone formulation A was manually applied to the Verso SCK sheet sample as described above, but in this case, the applied coating was passed under two focused 13 mm diameter D lamps mounted in tandem. The observations are as follows:
[0169] Conveyor speed, fpm Qualitative hardening
[0170] 200 Excellent curing; no migration, no staining, good settling
[0171] 250 Good curing; no migration, no staining, difficult to peel off
[0172] 275 Good curing; slight migration, slight staining, difficult to peel off
[0173] 300% cured; slight staining and migration residue, fast post-curing
[0174] Example 1E
[0175] Silicone formulation B has 99.0 parts M (Vi) D 80 M (Vi)It was prepared with a polymer, 1.0 parts acid-anhydride functional polymer AA containing [MeCp]PtMe3 catalyst sufficient to provide 85 ppm of platinum, and 8.3 parts [MeH]2Q crosslinking agent. Formulation B differed from Formulation A in that the amount of acid-anhydride functional silicone polymer was reduced to about 1% (w / w). Curing studies were performed using a Verso SCK substrate as described in the previous example.
[0176] Conveyor speed, fpm Qualitative hardening
[0177] 150 Excellent curing; no migration, no staining, good settling
[0178] 250 Good curing; no migration, no staining, good settling
[0179] 300 Good curing; slight migration, no staining, good settling
[0180] 350 did not meet curing standards; migration was observed, but rapidly improved with post-curing.
[0181] Curing performance was further improved by reducing the concentration of acid-anhydride functional silicone additive from 8.5% to 1%.
[0182] Example 1F
[0183] Silicone formulation C was prepared identical to formulation B above, except that the acid-anhydride functional silicone polymer AA was not present. For the purposes of this technology, Example 1F is considered a comparative example. Curing evaluation was performed in the same manner as in Examples 1A-1E.
[0184] Conveyor speed, fpm Qualitative hardening
[0185] 150 Cured; No migration, No staining, Poor adhesion (peels easily)
[0186] 250 Insufficient curing; stained surface and poor adhesion not improved by post-curing
[0187] Example 1G
[0188] Except for reducing the MeCpPtMe3 catalyst concentration to provide 50 ppm Pt, the formulation Formulation D, identical to B, was prepared. The results of the curing evaluation are listed below.
[0189] Conveyor speed, fpm Qualitative hardening
[0190] 100% cured; weak migration and staining occurred, post-curing observed
[0191] 150 under-curing; migration and staining improved with post-curing
[0192] 200% curing insufficient; good settling ability, but migration and staining occur
[0193] Examples 1A to 1G illustrate several methods by which the photo-hydrosilylation curing of vinyl silicon and hydride-silicon-based coatings using an R'CpPtR'3 catalyst can be significantly improved. Improved curing and products were observed using an iron-doped mercury vapor lamp, such as a Heraeus 'D' type, instead of a standard 'H' type mercury vapor lamp. Equipping a lamp housing with a dichroic reflector is another option for tuning or improving the curing. Finally, optimizing the content of acid-anhydride functional silicone polymer additives also contributes to improved curing speed and stability.
[0194] Example 2
[0195] The same M as described in Examples 1Aa to 1G (Vi) D 80 M (Vi) Vinyl silicone polymer, [M (H)Photo-hydrosilylation curing of different silicone formulations based on a 2Q crosslinking agent and an acid-anhydride functional silicone polymer AA was studied as a function of MeCpPtMe3 catalyst concentration, molar concentration of 2-isopropylthioxanthone (ITX) as % of the molar concentration of MeCpPtMe3, lamp type and number of lamps, and coating line speed, experiments were performed over a period of one year. 1% of the acid-anhydride functional polymer AA was present in all tested coatings. A quartz shield separating the lamp from the curing sample was present or absent. These experiments were performed on a pilot coating line equipped with a 5-roll film split silicone coater capable of laying down defect-free coatings 1 to 2 microns thick. UV curing radiation was provided by two or four banks of focused Hereaus microwave-fired 600-watt / inch D or H type UV lamps. Dichroic reflectors were installed in all experimental processes.
[0196] The silicone coating weight was calculated using XRF technology, which is common in the silicone liner industry. Silicone was applied to the Verso SCK described in Examples 1A through 1G. Qualitative curing of the samples was observed immediately offline, and post-curing was also observed. For these experiments, the quality of curing was assigned a numerical ranking, ranging from 0, indicating no curing, to 4, indicating excellent curing. From a performance perspective, a grade of 3 or 4 would be considered acceptable performance. For simplification, the table below includes only results yielding 3 or better. It should be noted that a 1-micron coating thickness is approximately 1 g / m².
[0197] Coating Mall % ppm Pt lamp Line speed fpm Coat weight gsm Q-Shield Hardening grade ITX 2A 50 4 x D 100 1.20 Yes 3 0 2B 80 4 x D 300 1.10 Yes 3 0 2C 85 4 x D 300 1.20 Yes 4 0 2D 100 4 x D 300 1.27 Yes 4 0 2D 100 4 x D 600 1.33 Yes 3 0 2E 120 4 x D 600 1.35 Yes 4 0 2E 120 2 x D 100 1.27 Yes 3 0 2G 85 4 x D 300 1.26 Yes 4 20 2H 85 4 x D 300 1.26 Yes 4 50 2J 100 4 x D 600 1.27 Yes 3 50 2K 100 2H+2D 300 1.30 Yes 3 50 2K 100 2 x H 200 1.40 Yes 4 50 2K 100 2 x D 200 1.40 Yes 3 50 2K 100 2 x D 300 1.35 NO 3 50 2K 100 2 x H 200 1.42 NO < 3 50 2K 100 2H+2D 300 1.35 NO 3 50 2K 100 4 x D 600 1.40 NO 3 50 2L 85 4 x D 500 1.35 NO 3 0 2O 85 4 x D 500 1.29 NO 3 100 2P* 85 4 x D 500 1.27 NO 3 50
[0198] * High SiH / vinyl ratio (2x normal crosslinker level)
[0199] Example 2 is an extensive series of experiments conducted in a manner that mimics the commercial production of silicone-coated release liners. The most significant difference between Example 1 and Example 2 is the much thicker silicone coating applied by the manual use of a #0 Meyer rod in the experiment described in Example 1. The multi-roll high-speed silicone coater on the pilot line used in the Example 2 experiment is the same type of coater found on commercial silicone coating lines. Sample coat weights of 0.8 to 2.0 gsm on the Verso SCK represent the micron-scale silicone thickness of industrial release liners, and the curing evaluation of these samples provides a realistic assessment of how variations in silicone formulation and processing affect the quality and commercial potential of photo-activated hydrosilylated cured silicone liners.
[0200] Example 2 demonstrates that under the conditions described above, a processing line speed of 500 to 600 fpm is achieved with a sufficient amount of MeCpPtMe3 to provide approximately 100 ppm Pt to the coating formulation. The data also show that while the D lamp may be better suited for MeCpPtMe3 photochemistry than the H lamp in the absence of a sensitizer, the addition of the ITX sensitizer slightly improves system performance when the H lamp is in use. Good adhesion of the cured silicone to the Verso SCK sheet was observed in all tests. The removal of the quartz shield improves curing to some extent, but all other factors remain the same.
[0201] Example 3
[0202] The third set of experiments was performed on the same pilot coating line as described in Example 2. In this case, different SiH-functional silicone crosslinker polymers were blended with two different vinyl-terminated linear polydimethylsiloxane base polymers. MeCpPtMe3 at a concentration providing 60 to 120 ppm of platinum was blended with the curable silicone mixture, and between 0 to 0.5% of acid-anhydride functional silicone polymer AA was also present in the coating formulation. None of the formulations contained an ITX sensitizer. The ratio of reactive SiH / vinylsiloxane varied between 2.0 and 2.05. As in Example 2, the line speed and silicone coat weight were varied, and the degree of curing was qualitatively evaluated as described above, and samples of the cured silicone liner were also quantitatively evaluated for curing by determining the weight % of extractable silicone present during exposure to concentrated UV light within minutes. Extraction was performed on a precisely measured small area of the liner placed in methyl isobutyl ketone solvent for several days prior to the analysis of the extractant liquid by atomic absorption technology. All experiments were conducted using four banks of 600-watt / in power Hereaus microwave-driven D lamps equipped with dichroic reflectors. These experiments varied the silicone formulation, substrate, and processing conditions to evaluate different processing conditions of UV-activated addition-cured release liners.
[0203] The formulation, processing conditions, qualitative curing, and % extractable silicone for selected test tasks that achieved well-cured silicone coatings are presented in the table below. Vinyl base polymer 1 is structural formula M (Vi) D 114 M (Vi) having; vinyl base polymer 2 has structural formula M (Vi) D 149 M (Vi) It has; the silanol-stopping polymer has the structural formula HO(Me)2SiO-D230 It has -OSi(Me2)OH. Crosslinking agent 3 is MD(H) a D b It has a linear structure of M (where D(H)=(CH3)(H)SiO and a and b are integers from 10 to 30). Crosslinking agents 4, 5, and 6 have structural formula MD (H) c It is a blend of a homopolymer of M (where c is an integer between 20 and 40) and crosslinker 3. Crosslinker 3 contains about 0.8% reactive hydride; crosslinker 4 contains about 1.04% hydride; crosslinker 5 contains about 0.96% reactive hydride; and crosslinker 6 contains about 0.88% reactive hydride. The substrate is a Verso SKP sheet (supercarinder-treated kraft), and the level of anhydride functional polymer AA is maintained at 0.5 wt% in all results summarized in Table 2.
[0204] coating base polymer crosslinking agent SiH / Vinyl ppm Pt Line speed Coat weight gsm Hardening grade % Extraction 3A 1 3 2.0 100 200 1.64 4 3.0 3A 1 3 2.0 100 400 1.77 3 3.7 3A 1 3 2.0 100 600 1.59 3 5.0 3B 1 3 2.0 120 200 1.77 4 3.0 3B 1 3 2.0 120 400 1.80 4 2.9 3B 1 3 2.0 120 600 1.72 4 3.0 3D 1 3 2.5 80 200 1.79 4 3.4 3D 1 3 2.5 80 400 1.74 3 3.9 3D 1 3 2.5 80 600 1.69 3 4.2 3E 1 3 2.5 100 200 1.77 4 2.9 3E 1 3 2.5 100 400 1.80 4 2.6 3E 1 3 2.5 100 600 1.79 3 2.9 3C 1 3 2.3 100 200 1.79 4 3.1 3C 1 3 2.3 100 400 1.77 4 3.9 3C 1 3 2.3 100 600 1.71 3 4.2 3D 1 3 2.5 80 200 1.79 4 3.3 3D 1 3 2.5 80 400 1.77 4 3.9 3D 1 3 2.5 80 600 1.79 4 4.2
[0205] The data in Table 2 demonstrate that the concentration of MeCpPtMe3 (expressed as ppm Pt) and the relative molar ratio of reactive SiH / vinyl can affect the curing grade and qualitative and quantitative crosslinking density, expressed as percent extractable siloxane, respectively. For example, a combination of 80 ppm Pt and a SiH / vinyl ratio of 2.0 or a combination of 120 ppm Pt and a SiH / vinyl ratio of 2.5 results in excellent curing and low extractables at processing rates of 200 to 600 fpm. Generally, commercial heat-treated solvent-free additive-cured silicone release agents are considered to be well-cured and stable upon contact with adhesives when the percent extractable siloxane is 5% or less; in most cases, 5 to 10% extractables will be reduced to less than 5% through post-curing within a short time after oven exposure. Therefore, based on this, it is evident that the selection of base polymer 1 and crosslinker polymer 3 combined with a 5% acid-anhydride functional additive polymer provides some flexibility in the concentration of the UV-active catalyst and the ratio of crosslinker to vinyl silicone base polymer in the processing of a release liner on a typical SCK substrate.
[0206] Next, a series of experiments were conducted to determine the effect of the crosslinking agent hydride content on the degree of addition curing of UV-activated platinum catalyst release coating formulations. The formulations, processing conditions, and results are listed in Table 3. The description is Verso SKP.
[0207] coating base polymer crosslinking agent SiH / Vinyl ppm PT Line speed Coat weight gsm Hardening grade % Extraction 3C 1 3 2.3 100 200 1.79 4 3.1 3C 1 3 2.3 100 400 1.77 4 3.9 3C 1 3 2.3 100 600 1.71 3 4.2 3T 1 4 2.3 100 200 1.80 4 7.2 3T 1 4 2.3 100 400 1.77 4 12.9 3T 1 4 2.3 100 600 1.8 4 14.0 3T 1 4 2.3 100 800 1.77 2.5 22.0 3D 1 3 2.5 80 200 1.79 4 3.4 3D 1 3 2.5 80 400 1.74 3 3.9 3D 1 3 2.5 80 600 1.69 3 4.2 3J 1 4 2.5 80 200 1.77 4 7.5 3J 1 4 2.5 80 400 1.82 4 13.0 3J 1 4 2.5 80 600 1.75 3 14.4 3J 1 4 2.5 80 800 1.54 2 22.5
[0208] It appears that there is a reaction from the UV-activated Pt catalyst system with respect to the hydride content (H content) of the crosslinking agent (single polymer or blend). A gradual increase in H content from crosslinking agent 3 (0.8% H) to crosslinking agent 4 (1.04% H) results in a large increase in % extractable silicon regardless of catalyst concentration or H / vinyl ratio. When extractable silicon is maintained at less than 15%, a qualitative curing grade of 3 to 4 is maintained.
[0209] The following set of experiments included two different base polymers and 0 or 0.5% of two polymers AA. The catalyst concentration was 100 ppm, and the SiH / vinyl ratio was 2.3:1.
[0210] coating base polymer crosslinking agent Polymer AA Line speed Coat weight gsm Hardening grade % Extraction 3H 1 4 0.5% 200 1.80 4 4.7 3H 1 4 0.5% 400 1.84 4 6.8 3H 1 4 0.5% 600 1.79 4 8.9 3L 2 4 0.5% 200 1.82 4 14.4 3L 2 4 0.5% 400 1.77 3 19.9 3L 2 4 0.5% 600 1.77 3 23.8 3I 1 4 0 200 1.79 4 7.2 3I 1 4 0 400 1.85 4 10.2 3I 1 4 0 600 1.79 3 14 3M 2 4 0 200 1.79 4 12.2 3M 2 4 0 400 1.79 3 23 3M 2 4 0 600 1.71 2 30.5
[0211] In this case, base polymer 2, a vinyl-stopped polydimethylsiloxane with a higher MW than base polymer 1, did not complete curing. Additionally, the presence of 0.5% polymer AA significantly aids in the completeness of curing, as evidenced by lower extraction and higher curing grades for coatings 3H and 3L versus 3I and 3M, respectively.
[0212] To better elucidate the relationship between MeCpPtMe3 concentration and the photocuring efficacy of the vinylsiloxane-hydridosiloxane crosslinking reaction, a series of trials were conducted with 2.3 SiH / vinyl at four different catalyst concentrations using base polymer 1 containing 0.5% polymer AA and crosslinking agent 4. The curing grade and % extractable siloxane were measured. The results are shown in Table 5.
[0213] coating base polymer crosslinking agent ppm PT Line speed fpm Hardening grade % Extraction 3R 1 4 120 200 4 4 3R 1 4 120 400 4 4.2 3R 1 4 120 600 4 5 3R 1 4 120 800 4 7.2 3S 1 4 100 200 4 4 3S 1 4 100 400 4 5 3S 1 4 100 600 4 7 3S 1 4 100 800 3 9 3T 1 4 80 200 4 7.2 3T 1 4 80 400 4 12.9 3T 1 4 80 600 4 14 3T 1 4 80 800 2 22 3U 1 4 60 200 4 9 3U 1 4 60 400 3.5 15.6 3U 1 4 60 600 3 20 3U 1 4 60 800 2 27.5
[0214] A catalyst concentration of less than 100 ppm combined with high SiH crosslinker 4 resulted in highly extractable siloxanes at the highest line speed, consistent with the previous example. Next, the curing efficacy of the system applied to Verso SKP paper was further investigated as a function of the hydride content of the crosslinker (Xlink %H) using a coating with the lowest catalyst concentration (60 ppm Pt). Treatment conditions, polymer AA loading, and a SiH / vinyl of 2.3 were maintained in all formulations listed in Table 6.
[0215] coating base polymer crosslinking agent Xlink %H Line speed Hardening grade % Extraction 3U 1 4 1.04 200 4 9 3U 1 4 1.04 400 3.5 15.6 3U 1 4 1.04 600 3 20 3U 1 4 1.04 800 2 27.5 3V 1 3 0.8 200 4 4 3V 1 3 0.8 400 3.5 5.5 3V 1 3 0.8 600 3.5 6 3V 1 3 0.8 800 3 7 3W 1 5 0.96 200 4 5 3W 1 5 0.96 400 3.5 7.7 3W 1 5 0.96 600 3.5 12 3W 1 5 0.96 800 2.5 20.5 3X 1 6 0.88 200 4 6 3X 1 6 0.88 400 3.5 11 3X 1 6 0.88 600 3 17.7 3X 1 6 0.88 800 2.5 21.5
[0216] Curing grade and % extractable silicon were inversely proportional to the % reactive hydride (SiH) present in the crosslinker, and the largest performance difference was observed between crosslinkers 3 and 4. Intermediate hydride levels for crosslinkers 5 and 6 led to extraction levels for cured coatings 3W and 3X, while such levels were between 3U and 3V. Following these tests, the photocuring of formulation 3U (60 ppm Pt catalyst loading applied at ~1.6–1.7 gsm⁻¹) was tested on several different paper substrates, and the results are shown in Table 7. Kruger sheets are a supercalendered kraft type.
[0217] coating base polymer crosslinking agent write Line speed fpm Hardening grade % Extraction 3U 1 4 Verso SKP 200 4 9.0 3U 1 4 Verso SKP 400 3.5 15.6 3U 1 4 Verso SKP 600 3 20.0 3U 1 4 Verso SKP 800 2 27.5 3U 1 4 Kruger 18121 200 4 7.0 3U 1 4 Kruger 18121 400 4 11.0 3U 1 4 Kruger 18121 600 4 15.6 3U 1 4 Kruger 18121 800 3.5 19.4 3U 1 4 Kruger 18121 200 4 6.8 3U 1 4 Kruger 18121 400 4 10.2 3U 1 4 Kruger 18121 600 4 12.7 3U 1 4 Kruger 18121 800 3.5 16.0 3U 1 4 UPM G58 Glassine 200 4+ 4.0 3U 1 4 UPM G58 Glassine 400 4+ 7.3 3U 1 4 UPM G58 Glassine 600 4+ 10.1 3U 1 4 UPM G58 Glassine 800 4 12.0
[0218] This data shows that specific paper substrates available from different vendors are highly suitable for use with UV-activated MeCpPtMe3 photo-hydrosilylation catalyst systems. For example, qualitatively cured and reduced extractability silicon was obtained using glassine sheets at a line speed of 800 fpm with a Pt concentration of 60 ppm when irradiated with four banks of D lamps as described above.
[0219] Tests on Evergreen poly-coated kraft (low-density polyethylene coated on unbleached kraft paper) having the same 3U silicone formulation applied at a coating amount of 1.5 gsm were performed at a line speed of 400 fpm, yielding a well-cured silicone coating with excellent adhesion to the polykraft liner substrate without damage to the polyethylene layer. It should be noted that heat-additive cured silicone release agents are difficult to cure on PK liners at temperatures that do not decompose or melt polyethylene, and thus demonstrate that a photocurable silicone system using a vinyl silicone base polymer and a SiH crosslinking agent together with a MeCpPtMe3 catalyst is particularly suitable for use on polykraft substrates.
[0220] Two coating formulations containing silanol-stopping polymers were also tested for qualitative curing; 3N was 90 parts vinyl-stopping polymer 1 and 10 parts silanol-stopping polymer HO(Me)2SiO-D 230 -OSi(Me2)OH, 0.5 parts polymer AA, 100 ppm Pt MeCpPtMe3, and crosslinker 4 sufficient to provide a SiH / vinyl ratio of 2.3 are used. 3O is a 75 / 25 / 0.5 analog of 3N. The 3N coating curing grade was evaluated as 4.0 when applied to Verso SKP sheets at a line speed of 600 fpm. The 3O coating curing grade was determined to be 3.0 at a line speed of 600 fpm. These results confirmed that silanol-suspended polydimethylsiloxane fluids or gums can be used as additives to modify the release properties, coverage, or other performance characteristics of these photocurable additive curing formulations. Platinum hydrosilylation catalysts are known to catalyze the SiOH + SiH → SiOSi + H2 condensation, and MeCpPtMe3 is no exception.
[0221] Example 4
[0222] The laboratory-scale UV processors described in Examples 1A, 1B, 1C, 1D, 1E, 1F, and 1G above were used to provide a qualitative curing evaluation (graded as in the preceding examples) of a combination of curing lamps containing a monochromatic 385 nm emitting LED source. MeCpPtMe 3 및 M derived from and having 100 ppm Pt (Vi) D 115 M (Vi) + MD (H) n D m Curable silicone formulations were prepared consisting of M (0.8% H content) and H / vinyl in a ratio of 2. 0.5 wt% of polymer AA was also present. The lamp combination included an LED curing lamp array as a standalone component and was combined with microwave-driven D lamps of 13 mm and 9 mm diameter equipped with dichroic reflectors. Hand draw-downs of Verso SKP sheet samples having an average coat weight of approximately 1.3 gsm (=g / m²) were exposed to the concentrated curing lamps at different conveyor line speeds. The experimental and observational results are listed in Table 8.
[0223] lamp Conveyor speed, fpm Qualitative hardening grade 385 nm LED 3 x 50 0 (no hardening) 13 mm D lamp 50 3.5 LED + 13 mm D 50 4 13 mm D lamp 100 3 LED + 13 mm D 100 4 13 mm D lamp 200 1.5 LED + 13 mm D 200 2.5 9 mm D lamp 100 3.5 LED + 9 mm D 100 4 LED + 9 mm D 200 3.5 9 mm D + LED 200 2.5 (reverse ramp order)
[0224] As shown in Example 4, exposure to 385 nm wavelength LED radiation does not initiate photo-hydrosilylated curing of this coating, but exposure to 385 nm LED light prior to exposure to an iron-doped mercury vapor (D) lamp provides faster curing than the D lamp itself. The sharper focus of the narrower 9 mm diameter D bulb promotes significantly better curing of the coating than observed with the 13 mm diameter lamp. The poor curing observed with D lamp exposure preceding LED lamp exposure suggests that the thermal output of the LED source is more important for system curing than 385 nm absorption by the catalyst.
[0225] Example 5
[0226] A series of photo-DSC experiments were performed using a TA Instruments differential scanning calorimeter equipped with a UV lamp for sample irradiation to determine how preheating a curable blend of vinylsilicon base polymer 1 and hydride crosslinker polymer 3 before exposure to UV light affects the photocuring rate. The programmed experimental sequence consisted of the following steps and was executed:
[0227] 1) An equilibrium step for setting the target temperature of the above sample;
[0228] 2) Dark hold for 30 seconds at the above target temperature;
[0229] 3) 0.6 second UV light exposure;
[0230] 4) Maintain at the target temperature for 1 minute.
[0231] Steps 3 and 4 were repeated 8 times for 9 individual exposures to UV light passed through a 280 to 450 nm bandwidth filter, which was a very good radiance for the Heraeus D lamp. A curable mixture of 10 g of vinylsilicon base polymer 1 and hydride-functional silicone crosslinker 3 was mixed with 0.05 g of anhydride functional polymer AA using a MeCpPtMe3 catalyst sufficient to supply 50 or 25 ppm Pt. The H / vinyl ratio was maintained at 2.0. 14–18 mg of the catalytic formulation sample was dropped into the sample pan mounted on the instrument along with reference pans. An exothermic hydrosilylation reaction was observed for each sequential pulse of UV light by calorimetric response and expressed as a percentage of the total exothermic reaction resulting from all 9 UV pulse exposures. The sample temperature was limited to a range of 25 to 80 ℃: The results are shown in Table 2 below:
[0232] Table 9: 50 ppm Pt formulation
[0233] Isothermal temperature ℃ Primary exposure, fever rate % Secondary exposure, fever rate % 4th exposure, fever rate % 6th exposure. Fever rate % 25 49.8 75.7 84.0 90.4 50 74.7 81 86.2 95.0 60 80.7 87.6 93.3 97.0 70 85.4 88.3 92.3 95.3 80 75.8 83.3 88.0 92.0
[0234] Table 10: 25 ppm Pt formulation
[0235] Isothermal temperature ℃ Primary exposure, fever rate % Secondary exposure, fever rate % 4th exposure, fever rate % 6th exposure, fever rate % 25 66.8 83.8 89.6 93.3 50 83.2 88.2 93.3 98.1 80 84.3 87.4 91.9 95.1
[0236] The ideal photo-DSC reaction is that an initial 0.6-second exposure would result in the complete reaction of vinyl and SiH available in the formulation (100% exothermic). These experiments indicated that gentle heating of the curable formulation prior to UV light exposure clearly accelerates the photo-reaction and thus reduces post-curing. In all cases, the reaction is essentially complete after 6 x 0.6-second exposures to UV light (> 90%), but preheating the curable sample to 70°C (in the presence of 50 ppm Pt) results in an increase of approximately 50% to 85% of the reaction percentage in a single exposure. The unusual 80°C result appears to be caused by heat in the dark prior to initial UV exposure promoting the thermal (crosslinking) reaction, thereby limiting the crosslinks available through photoactivation. A similar effect was observed when the concentration was reduced to 25 ppm Pt.
[0237] Therefore, a MeCpPtMe3-catalyzed photocurable silicon coating can be crosslinked more effectively and rapidly by a dual-cure process in which the coated substrate is passed under a UV curing lamp in a warmed state after passing it through a mild heat from an oven or IR lamp radiation. Heating the coated formulation and the substrate to which it is applied to 60°C to 120°C prevents or minimizes moisture retention of the paper substrate or damage to the film or plastic-coated paper substrate, and makes the subsequent UV curing faster and more complete than UV exposure alone.
[0238] The foregoing includes embodiments of the present invention. Of course, it is not possible to describe every conceivable combination of purposes or methodologies for describing the present invention, but a person skilled in the art will recognize that many additional combinations and permutations of the present specification are possible. Accordingly, the present specification is intended to include all such changes, modifications, and variations that fall within the spirit and scope of the appended claims. Furthermore, to the extent that the term 'comprising' is used in the detailed description or claims, such term is intended to be inclusive in a manner similar to how 'composed of comprising' is interpreted when used as a transition in a claim.
[0239] The foregoing description identifies various non-limiting embodiments of photocurable silicone compositions, coatings formed from such compositions, articles comprising such coatings, and methods for forming such coatings and articles. Modifications may occur to those skilled in the art who are capable of making and using the present invention. The disclosed embodiments are for illustrative purposes only and are not intended to limit the scope of the invention or the subject matter described in the claims.
Claims
Claim 1 As a photocurable silicone composition, (i) vinyl functional polysiloxane M of formula (Ia) 1vi D 1vi c D 2 d M 1vi (Ia)(here, M 1vi is (R 1 )(R 2 )(CH2=CH)SiO 1 / 2 Igo; D 1vi is (R 6 )(CH2=CH))SiO 2 / 2 is; D 2 is (R 7 )(R 8 )SiO 2 / 2 and; R 1 , R 2 , R 6 , R 7 and R 8 (ii) hydride functional siloxane; (iii) Formula (1) R 19 CpPtR 20 3(here R 19 and R 20 Each is independently selected from C1-C10 alkyl groups, Cp is a cyclopentadienyl group, and the bond between Cp and Pt is eta It is a combination); Equation (2) [(R 29 ) a (R 30 ) b Cp]Pt(R 31 ) 3 (Here, R 29 ga is a C7-20 aromatic organic group, and R 30 and R 31 Each of these is independently a C1-22 aliphatic organic group, Cp is a cyclopentadienyl group, "a" is an integer from 1 to 3, "b" is an integer from 0 to 3, and the sum of a + b is 1 to 4); and / or formula (3) [(R 32 ) c (R 33 ) d Cp]PtR 34 R 35 Q (here, R 32 ga is a C6-20 aromatic group, and R 33 , R 34 , and R 35 A photocurable silicon composition comprising: (iv) a photoactive catalyst selected from one or more platinum-cyclopentadiene complexes in which each is independently a C1-22 aliphatic organic group, Cp is a cyclopentadienyl group, Q is a silicon-containing organic sensitizing group, "c" and "d" are each independently integers from 0 to 5, and the sum of "c + d" is 0 to 5, and present in an amount sufficient to provide 50 to 150 ppm of platinum; and (iv) an acid-anhydride functional polysiloxane present in an amount of 0.1 to 10 parts by weight based on the total weight of the photocurable silicon composition. Claim 2 delete Claim 3 delete Claim 4 In claim 1, the photocurable silicone composition wherein the hydride functional siloxane has the following formula (II): M 3H h M 4 i D 3H j D 4 k T 3H l T 4 m Q 2 n (II)(here, M 3H = (R 10 )(R 11 )(H)SiO 1 / 2 M 4 = (R 12 )(R 13 )(R 14 )SiO 1 / 2 D 3H = (R 15 )(H)SiO 2 / 2 D 4 = (R 16 )(R 17 )SiO 2 / 2 T 3H = (H)SiO 3 / 2 T 2 = (R 18 )SiO 3 / 2 Q 2 = SiO 4 / 2 and, here, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 Each of these is independently a C1-C10 saturated hydrocarbon group; and the subscripts h, i, j, k, l, m, and n are 0 or positive numbers, provided that 2 ≤ h+i+j+k+l+m+n < 1000 and h+j+l is greater than 0). Claim 5 In claim 4, a photocurable silicone composition in which the hydride functional siloxane has the following formula (IIb); M 4 D 3H j M 4 (IIb) ( where, M 4 , D 3H and M 4 (As defined above, and j is 10-40). Claim 6 In claim 4, a photocurable silicone composition in which the hydride functional siloxane is a copolymer of the following formula (IIa); M 4 D 3H j D 4 k M 4 Q 2 (IIa)(here, M 4 , D 3H , D 4 , M 4 and Q 2 (As defined above, and j+k is 10-40). Claim 7 delete Claim 8 A photocurable silicon composition according to claim 1, wherein the photoactive catalyst is the Pt(IV) compound methylcyclopentadienyltrimethylplatinum. Claim 9 In claim 1, a photocurable silicone composition wherein the acid-anhydride functional polysiloxane (iv) is a compound of the following formula; M 5A D 5 o D 6A p D 7H q M 5A (Here, M 5A Ga (R 21 )(R 22 )(R 23 )SiO 1 / 2 and, D 5 Ga (R 24 )(R 25 )SiO 2 / 2, is, D 6A Ga (R 26 )(R 27 )SiO 2 / 2 and, D 7H Ga (R 28 )(H)SiO 2 / 2 and, here, R 21 , R 22 , R 24 , R 25 , R 26 and R 28 Each is independently a C1-C10 saturated hydrocarbon radical; R 23 and R 27 Each of these represents an acid-anhydride functional group that can be independently derived from the reaction of allyl succinic anhydride and a Si(H) functional group; where o + q is 10-40 and p is 1-20). Claim 10 A photocurable silicone composition comprising, in addition to a siloxanol resin, the 1st version. Claim 11 A photocurable silicone composition according to claim 1, wherein the ratio of hydride groups to vinyl groups is 0.5:1 to 10:
1. Claim 12 A photocurable silicone composition according to claim 1, wherein the ratio of hydride groups to vinyl groups is 1.5:1 to 3:
1. Claim 13 A photocurable silicone composition according to claim 1, wherein the ratio of hydride groups to vinyl groups is 2:1 to 2.5:
1. Claim 14 A photocurable silicone composition according to claim 1, wherein the vinyl functional polysiloxane (i) is present in an amount of 80 to 99 parts by weight; the hydride functional siloxane (ii) is present in an amount of 1 to 20 parts by weight; the acid-anhydride functional polysiloxane (iv) is present in an amount of 0.1 to 10 parts by weight; and the photoactive catalyst (iii) is present in an amount sufficient to provide 50 to 150 ppm of platinum, each of which is based on the total weight of the composition. Claim 15 A method for forming a silicon film on a substrate, comprising: (a) applying a photocurable silicon composition of any one of claims 1, 4 to 6 and 8 to 14 to the surface of a substrate; and (b) exposing the photocurable silicon composition to a UV light source having a wavelength of 25 nm to 400 nm. Claim 16 In paragraph 15, the method wherein the UV light source is an H+ mercury vapor type UV lamp. Claim 17 In paragraph 15, the method wherein the UV light source is a D-type iron-doped mercury vapor UV lamp. Claim 18 In claim 15, a method wherein the substrate comprising the photocurable silicone composition is transported at a speed of 20 feet / min to 1,000 feet / min. Claim 19 A method according to claim 15, further comprising the step of concentrating light from the UV light source onto the photocurable silicon composition using one or more reflectors. Claim 20 A method according to claim 15, further comprising the step of exposing the photocurable silicon composition and the substrate coated with the photocurable silicon composition to a heat source before exposing the photocurable silicon composition to the UV light source. Claim 21 A method according to claim 20, wherein the heat source is selected from an oven, an infrared lamp, an LED light source, or a combination thereof. Claim 22 A method according to claim 20, wherein the photocurable silicone composition and the substrate coated with the photocurable silicone composition are heated to a temperature of 25°C to 120°C. Claim 23 In paragraph 15, the above description is selected from one or more of glassine paper, supercalendered kraft (SCK) paper, clay-coated kraft (CCK) paper, polyethylene, polypropylene, polyester, polyethylene-kraft paper (PK), or polypropylene-kraft paper (PPK). Claim 24 An article comprising a coating formed from a photocurable silicone composition of any one of claims 1, 4 to 6 and 8 to 14 disposed on the surface of a substrate. Claim 25 Article 24, wherein the article is a release liner, and the substrate is selected from one or more of glassine paper, supercalendered kraft (SCK) paper, clay-coated kraft (CCK) paper, polyethylene, polypropylene, polyester, polyethylene-kraft paper (PK), or polypropylene-kraft paper (PPK). Claim 26 An adhesive article comprising an adhesive-backed substrate that is in releaseable contact with a release layer, wherein the release layer comprises a coating formed from a photocurable silicone composition of any one of claims 1, 4 to 6 and 8 to 14. Claim 27 An article comprising a substrate having a silicone film formed by the method of claim 15.
Citation Information
Patent Citations
Curable silicone mold-releasing agent composition and cooking sheet using the same
JP2007302775A
Acid anhydride group-containing organosiloxane and method for producing the same
JP2013129691A
Release paper composition with excellent adhesion to paper and polymer film
JP2006519893A
Ultraviolet-curable adhesive organopolysiloxane composition
JP2015110752A
Use of light-activated hardenable silicon compositions for the production of thick-walled moulded articles or thick-walled coatings
KR1020070041764A